6G endogenous security:blockchain technology - Kaijun NIE; Bin CAO; Mugen PENG (Dianxin kexue)
With the development of mobile communication technology towards marginalization and distributed structure,the traditional network security method of external border protection will be faced with more and more challenges.The emerging network security accidents also show that it is necessary to grow self-adaptive,independent and self-growing security capabilities from the information system,that is,endogenous security.Blockchain,as a de-centralized shared ledger and database,has the characteristics of decentralization,immutability,leaving traces throughout,traceability,collective maintenance,openness and transparency,etc.,which can greatly meet the needs of endogenous security design.Therefore,the necessity and demand of endogenous security was described,then the blockchain technology as an important means to realize endogenous security was introduced,the main research progress,difficulties and challenges faced by blockchain were analyzed,and the future research direction and oppor-tunities were put forward.